Effects of interleukin‐17A in nucleus pulposus cells and its small‐molecule inhibitors for intervertebral disc disease. Issue 11 (11th September 2018) - Suyama, Kaori; Sakai, Daisuke; Hirayama, Noriaki; Nakamura, Yoshihiko; Matsushita, Erika; Terayama, Hayato; Qu, Ning; Tanaka, Osamu; Sakabe, Kou; Watanabe, Masahiko
Abstract: Intervertebral discs (IVD) degeneration, which is caused by ageing or mechanical stress, leads to IVD disease, including back pain and sciatica. The cytokine interleukin (IL)‐17A is elevated in NP cells during IVD disease. Here we explored the pharmacotherapeutic potential of IL‐17A for the treatment of IVD disease using small‐molecule inhibitors that block binding of IL‐17A to the IL‐17A receptor (IL‐17RA). Treatment of NP cells with IL‐17A increased expression of cyclooxygenase‐2 (COX‐2), IL‐6, matrix metalloproteinase (MMP)‐3 and MMP‐13. These increases were suppressed by an IL‐17A‐neutralizing antibody, and small molecules that were identified as inhibitors by binding to the IL‐17A‐binding region of IL‐17RA. IL‐17A signalling also altered sulphated glycosaminoglycan deposition and spheroid colony formation, while treatment with small‐molecule inhibitors of IL‐17A attenuated this response. Furthermore, mitogen‐activated protein kinase pathways were activated by IL‐17A stimulation and induced IL‐6 and COX‐2 expression, while small‐molecule inhibitors of IL‐17A suppressed their expression. Taken together, these results show that IL‐17A is a valid target for IVD disease therapy and that small‐molecule inhibitors that inhibit the IL‐17A–IL‐17RA interaction may be useful for pharmacotherapy of IVD disease.